The Role of BSBA Teachers on Students' Entrepreneurial Mindset and Skills at the College of Management and Accountancy - Castillo, Manuel P.; Estremera, Jann Mark M. (Advances in Social Sciences Research Journal, 2023)
This study investigates the pivotal role of Bachelor of Science in Business Administration (BSBA) teachers in shaping students' entrepreneurial mindset and developing their entrepreneurial skills. The entrepreneurial mindset encompasses attitudes and characteristics conducive to creative thinking, calculated risk-taking, perseverance, and adaptability. Meanwhile, entrepreneurial skills encompass practical abilities such as problem-solving, communication, leadership, and innovation. The study explores the influence of BSBA teachers on creativity, problem-solving, risk assessment, decision-making, teaching methods, and instructional approaches. The research draws upon a diverse range of theoretical perspectives, with an emphasis on experiential learning as a dynamic teaching approach that actively engages students in problem-solving, risk assessment, and decision-making. Employing a descriptive and correlational research design, the study collected data from BSBA students enrolled in a college of management and accountancy. The research utilized both descriptive and inferential statistics to analyze the collected data from a sample of 200 BSBA students. The results reveal a strong consensus among students on the significant impact of BSBA teachers on their entrepreneurial mindset and skills. Teaching methods that incorporate visual aids and interactive approaches received particularly high agreement, as did instructional methods focusing on experiential learning. The data also suggests a link between students' demographic profiles, college year level, and their perceptions of the impact of BSBA teachers on their entrepreneurial skills. The findings reject the null hypothesis that there is no significant relationship between student profiles and the role of BSBA teachers in entrepreneurial skills development. It is evident that BSBA educators hold a crucial position in nurturing an entrepreneurial mindset and refining entrepreneurial proficiencies in students. Their involvement with inventive pedagogical techniques, experiential methodologies, and practical illustrations profoundly shapes students' capacity for innovative thinking, proficient problem-solving, prudent risk assessment, and well-informed decision-making. This research serves to enhance comprehension regarding efficacious educational strategies in advancing entrepreneurship within the framework of the BSBA curriculum.